2010
DOI: 10.1007/s11102-010-0257-0
|View full text |Cite
|
Sign up to set email alerts
|

Pasireotide, an IGF-I action inhibitor, prevents growth hormone and estradiol-induced mammary hyperplasia

Abstract: Mammary hyperplasia increases breast cancer risk. Tamoxifen prevents breast cancer in women with atypical hyperplasia, but has serious side effects. As estradiol action requires IGF-I, direct inhibition of IGF-I action theoretically might be an efficacious alternative to tamoxifen. After hypophysectomy and oophorectomy, 21-day-old female rats were treated with GH and E₂. After 7 days all terminal end buds (TEBs) and 75% of ducts became hyperplastic. Co-treatment with pasireotide, a somatostatin analog that blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…A recent study demonstrated that SOM230 has a proapoptotic effect on rat mammary gland hyperplastic cells, mediated through sstr3 21 . Analogously, our study demonstrated a significant increase in apoptotic events as evidenced by a TUNEL assay, which demonstrated increased DNA fragmentation in the pancreata of mice treated with SOM230 vs. the pancreata of mice treated with PBS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that SOM230 has a proapoptotic effect on rat mammary gland hyperplastic cells, mediated through sstr3 21 . Analogously, our study demonstrated a significant increase in apoptotic events as evidenced by a TUNEL assay, which demonstrated increased DNA fragmentation in the pancreata of mice treated with SOM230 vs. the pancreata of mice treated with PBS.…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly targeting IGF1R signaling can also be achieved by using somatostatin or its analogues such as pasireotide (SOM230), which is approved as a therapy in the United States and Europe for conditions including Cushing's disease and acromegaly, and it acts to reduce growth hormone production and consequently IGF-1 production and signaling (Kleinberg et al 2011, Lewis et al 2014. In another indirect approach, metformin, a standard treatment for type 2 diabetes, is shown to inhibit crosstalk between InsR/IGF1R and EGFR and as a result has indirect effects on IGF-1 signaling (Rozengurt et al 2010, Liu et al 2011.…”
Section: :11mentioning
confidence: 99%
“…Tamoxifen therapy causes unpleasant side effects leading to a drastic diminishment in its use in more recent years (102, 103). There are investigations into IGF1R inhibitors as preventative therapies, but these are toxic as well and therefore again only will be helpful in high-risk women (104106). With the age of FFTB rising and the lack of preventative options, discovering the most important mechanisms underlying the protective effect of an early FFTB is imperative to developing prevention strategies for young healthy women (11, 107).…”
Section: Discussionmentioning
confidence: 99%